EFFECTS OF GROUP-BASED EXTENSION METHODS ON KNOWLEDGE AND PRODUCTION OF VEGETABLES AMONG DRY SEASON FARMERS IN SOUTHWESTERN NIGERIA (2014)
There are lots of constraints facing dry season vegetable production in Nigeria which can be corrected using the group-based extension services platform. Previous studies have focused on individual extension approaches that can only attend to one farmer at a time, thus limiting information dissemination. This study, therefore, investigated the effects of Farmers-Field School (FFS) and Demonstration Extension Methods (DEM) on knowledge and production of vegetables among dry season farmers in Southwestern Nigeria. The study adopted a pretest-posttest, control group, quasi-experimental design with 2x2x3 factoral matrix. The participants were 233 dry season farmers (197 males; 36 females) with primary (123), secondary school (92) and tertiary (18) educational background respectively drawn purposively from Oyo (Experimental 38; Control 40), Osun (Experimental 43; Control 35) and Ogun (Experimental 45; Control 32) states. The FFS and DEM extension methods were used to introduce new vegetable varieties, drilling method of planting and fertiliser application as well as use of organic manure to participants in experimental groups while control groups employed traditional methods of vegetable production. Celosia species and Amaranthus species were two leafy vegetables involved in the study. Treatment lasted for 16 weeks after which the knowledge, adoption of improved technologies, yield of vegetables, income and expenditure of dry season farmers in both the experimental and control groups were compared. Seven hypotheses were tested at 0.05 significance level. Data were analysed using (Analysis of co-Variance) ANCOVA and Scheffe post hoc tests . There was a significant main effect of treatment on knowledge of improved technologies by participants in experimental groups (F(6,226)=4.27, η2= 0.86). Oyo recorded highest level of increase in knowledge of improved technologies, followed by Osun and Ogun respectively. There was a significant main effect of treatment on adoption of improved technologies (F(6, 226,) = 8.83; η2= 0.163). Highest level of adoption of improved technologies was recorded in Osun followed by Ogun and Oyo respectively. There was a significant main effect of treatment on yields (kg) of vegetable production of participants UNIVERSITY OF IBADAN LIBRARY vi in experimental groups (F(6, 226)=2.88, η2=0.06), Oyo had highest increase in yields followed by Osun and Ogun respectively. There was a significant main effect of treatment on income on vegetable production (F(6, 226) = 3.41, η2= .070). Highest increase in income was recorded in Ogun, followed by Osun and Oyo respectively. There was a significant main effect of treatment on reduction of dry season farmers‘ expenditure (F(6, 226) = 4.40; η2 = .089); Oyo had the highest expenditure reduction followed by Ogun and Osun respectively. The male participants adopted the new technologies more than the female. Likewise, the level of adoption of new technology was higher among the participants with high level of education than with medium and low levels of education respectfully. Group-based extension methods enhanced knowledge, new technology adoption, crop yield, and income of dry season vegetable farmers in Southwestern Nigeria. Thus, agricultural extension workers should be encouraged to adopt the use of two or more group-based extension methods to disseminate agricultural information to such categories of farmers. Keywords: Group-based extension, Vegetable production, Dry season farming. Word count: 496